Attitude of stakeholders towards the organic law for the Bangsamoro autonomous region in Muslim Mindanao (OLBARMM) - Yasmira P. Moner; Sittie Akima A. Ali; Safa D. Manala-O (Cogent Social Sciences)
This study aims to contribute to the policy discourse on the Bangsamoro peace process by examining the affect, behavior, cognition and attitude of stakeholders towards the Organic Law for the Bangsamoro Autonomous Region in Muslim Mindanao (OLBARMM) using the Tripartite Theory of Attitude. The study used a mixed methods research design, and conducted both survey and personal interviews. PLS-SEM and PLS-MGA determined the significant factors that affect the attitude towards OLBARMM and the significant differences by age and province. Quantitative findings of the study reveal that, in the overall model, both affect and behavior significantly and positively influence the attitude of respondents towards OLBARMM while cognition does not. This implies that feelings and actions are stronger determinants of attitude than actual knowledge of the law. Age did not emerge as a significant moderating variable, meaning that both younger and older respondents appear to follow a similar pattern with respect to attitude formation. Province however emerged as a significant moderating variable in terms of cognition, revealing that respondents from Maguindanao tend to rely on their knowledge of OLBARMM more than respondents from Lanao del Sur in deciding their overall attitude towards the law. Moreover, qualitative findings have further revealed that there is a general positive feeling towards OLBARMM however there are also critical challenges that must be addressed. The stakeholders have voted for OLBARMM but continue to harbor some apprehension and doubt as to its effectiveness. They are hopeful that it will be a tool to develop and stabilize the region.